Mixed Small Cell Carcinoma and Mucinous Adenocarcinoma of Appendix: A Rare Case Report with Review of Literature - Sukumaran, Renu; Anoop, Thattungal Manoharan (Annals of Pathology and Laboratory Medicine, 2024)
Gastrointestinal mixed neuroendocrine non-neuroendocrine neoplasms (MiNEN) are a heterogeneous group of tumors showing different morphological and prognostic features. The biological behavior of MiNEN is mostly driven by its high-grade component. Due to limitations in diagnostic methods and poor awareness, the incidence of MiNEN may be underestimated. The pathogenesis of MiNEN remains controversial. Molecular studies point towards a common monoclonal origin of the two components. Mixed tumors of the appendix are quite rare compared with those occurring elsewhere in the gastrointestinal tract. Although the appendix represents a common site of intestinal neuroendocrine tumors, primary extrapulmonary small cell carcinoma of the appendix is a rare entity. We describe a unique case of primary combined adenocarcinoma and small cell carcinoma of the appendix.